Pengaruh ekspor, utang luar negeri dan nilai tukar terhadap cadangan devisa Indonesia - Renilda; Nurlina, Nurlina; Asnidar, Asnidar (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
The purpose of this study is to determine the effect of Exports, Foreign Debt, and Exchange Rates on Foreign Exchange Reserves in Indonesia. This study uses secondary data from 2008–2022 from the Central Statistics Agency and Bank Indonesia. Multiple linear regression analysis is used for time series data. The results of the study indicate that, partially, the Export and Foreign Debt variables have a positive and significant impact on Indonesia's Foreign Exchange Reserves; conversely, the Exchange Rate variable has a negative and significant impact on Indonesia's Foreign Exchange Reserves. Simultaneously, the Export, Foreign Debt and Exchange Rate variables have a significant effect on Foreign Exchange Reserves in Indonesia.